Optimal distribution of power under stress on power grid in real-time by reactive compensation-management and development in balance - Tadjeddine Ali A.; Arbaoui I.; Hamiani H.; Chaker A. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The industrial development, lifestyle and modernization of the management sectors in Algeria have led to an increase in demand for electricity power in recent years and an increase in demand for the energy sector. This high demand for power has led to problems with voltage drops, particularly as regards the quality of this voltage during periods peak load. Thanks to research on the development of the electricity transmission system in the South-West region of Algeria and based on the theoretical results. We have obtained an optimal solution for the location of the regulation systems for voltage and the frequency in the substations that exhibit strong violations and periodic static destabilization, in particular, the stations at the end of the 220Kv transmission lines. The techniques of modeling and controlling the voltage per frequency (Hz/V) as well as the critical analysis variants have been studied and confirmed using advanced real-time numerical simulation.